Characteristics investigation and synergistic anticancer effects of immobilized l-asparaginase onto iron-gold core-shell combined with cold atmospheric pressure plasma. (March 2023) - Montazeri, Ali Reza; Moghimi, Hamid; Ghourchian, Hedayatollah; Maghami, Parvaneh
Abstract: The 11-mercaptoundecanoic acid (11MUA) functionalized magnetic core-shell nanoparticles (Fe3 O4 @Au-MUA NPs) were produced and used to improve the properties of L -asparaginase (L -ASNase) and to increase the anticancer effects of the cold atmospheric pressure plasma (CAPP). SEM and TEM images confirmed the spherical shape of the NPs and showed that the average diameter of the NPs was 85 nm. Immobilized L -ASNase showed slight changes in the kinetics parameters of Vmax (from 227.27 ± 24.5 to 175.43.25.6 μM min −1 mg −1 ) and a decrease in Km (from 5.45 ± 0.18 to 4.052 ± 11 mM). The immobilized enzyme conserved 80 % of its activity after 4 h of incubation at 55 °C and lost 15 % of its activity after 14 consecutive cycles. MTT assay showed that CAPP combined with L -ASNase immobilized onto the Fe3 O4 @Au had the highest anticancer effect against cancer cells which decreased the viability of these cells by 43 %. The obtained results confirmed the improvement of enzyme features after immobilization and creating the synergistic anti-cancer effect in the simultaneous use of immobilized enzyme and cold atmospheric plasma. Therefore results suggested that Fe3 O4 @Au can be considered a prominent carrier for L -ASNase immobilization, and the use of immobilized L -ASNase with CAPP radiation can be accounted as an appropriate candidate for cancer therapy. Graphical Abstract: ga1 Highlights: 11-mercaptoundecanoic acid functionalized Fe3 O4 @Au NPs were synthesized. Functionalized Fe3 O4 @Au NPs showed an improved immobilization yield (79.27 %). Improvement of L -ASNase anti-cancer and kinetic features after immobilization. Synergic anti-cancer effect of immobilized L -ASNase with plasma radiation. L -asparagine shortage, Reactive Oxygen and Nitrogen Species kill cancer cells.